Investigating the moderating effect of market trends on the relationship between customer relationship management and customer performance in microfinance institutions - Rusul Hisham, Abdullah Alabdan (2024)
The purpose of this research is to determine the impact of customer relationship management on customer performance with the independent variable dimensions, such as needs, segment, and knowledge, and the dependent variable dimensions, which comprise customer satisfaction and customer loyalty, along with the effect of market trend moderating the relationship between customer relationship management and customer performance with moderation dimensions like saving, security, and purchasing power. A survey was conducted on Selangor's customers and employees of microfinance institutions as samples. A total of 294 usable questionnaires were collected. However, the research targeted 150 customers and 98 employees, and they were statistically analysed. A total of 24 hypotheses were constructed; six were used to analyse the relationship between CRM and customer performance. These were deemed partially supported, yet the other 18 positively supported hypotheses incorporated the relationship between CRM, market trends, and customer performance. Customer relationship management as the independent variable was found to have a positive but insignificant effect on customer performance as the dependent variable. For such a reason, it was only considered to be partially related. For the moderating variable, the market trend positively and significantly affected both the independent and dependent variables. Furthermore, it was found that customer relationship management and market trends influenced customer performance behaviour. However, the results showed and supported the effects caused by the market trend moderation, and it must be noted that for CRM to be effectively utilised, it requires moderation. Hence, the significance of the moderation effect and the overall study of this aspect is emphasised since little to no studies have moderated the effect of CRM on customer performance. This finding confirms the expectancy and social exchange underpinning theories, which submit that exchanging financial services towards more non-financial customer requirements leads to higher expectations for institutions and customers with excellent management. Similarly, this study's findings also established that the market trend is a positive moderator and enhancer complementary to needs, segmentation, knowledge, customer satisfaction, and customer loyalty—the effect of moderating in ensuring that satisfaction and loyalty are guaranteed in microfinance institutions. For customer performance in microfinance institutions, more emphasis should be placed on improving customer savings and security, considering customer purchasing power, the institution's CRM towards the needs, segmenting customers, and acquiring and sharing knowledge. Simultaneously, microfinance institutions must be strengthened to ensure that performance measures are tightened and adhered to.